THE EFFECT OF OWNERSHIP STRUCTURE ON COMPANY VALUE IN NON-FINANCIAL ISSUERS, 2016 – 2020 - Imaduddin, Adim (2023)
The ownership structure is one of the corporate governance mechanisms that can affect the company's agency costs. Besides that, it influences the company performance and maximization of company value. Due to the inconsistencies in the results of research regarding ownership structure on corporate value, this study aims to to determine the effect of institutional, foreign, and individual ownership and corporate value on non-financial issuers in 2016 – 2020. The method used was quantitative research using the correlation method. The data analysis technique used was multiple regression analysis and testing of classical assumptions and hypotheses. Hence, the study results concluded that Institutional Ownership, Foreign Ownership and Individual Ownership have a significant effect on Firm Value.